Tuntunan parenting dalam Islam: Merujuk pada surah Luqman ayat 13-19 - Jamil, Dina Rahmatun Najma (Maliki Interdisciplinary Journal, 2025)
In understanding the importance of the message and values of Islam in educating children, it is important to understand parenting and the importance of effective communication between parents and children. Islamic Parenting is a parenting concept that combines Islamic principles with modern parenting practices. In Islam, the family is considered the primary institution for character formation and child education. Parents have the responsibility to guide their children spiritually, morally, and intellectually. This process begins early on by teaching religious values, noble morals, and proper ethics. Surah Luqman verses 13-19 provide important guidance for parents in educating their children. Three main values highlighted in this surah are faith in Allah, respecting parents, and patience in facing trials. Luqman al-Hakim emphasizes the importance of avoiding associating partners with Allah, instilling gratitude towards parents, and building a good relationship with Allah through prayer. This article also highlights Islamic educational practices that can be applied in educating children, including nurturing with compassion, teaching to reject polytheism, strengthening faith, and awareness of Allah’s supervision. By understanding and applying the values contained in surah Luqman verses 13-19, it is hoped that parents can play a more effective role in shaping the character and morality of their children in accordance with Islamic teacinghs.